2015
DOI: 10.1002/pssc.201400275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment of CZTS absorber layer by ammonia solution

Abstract: In this work, we investigated the effect of surface treatment of the Cu2ZnSnS4 (CZTS) thin films using ammonia solution. CZTS thin films were prepared by RF sputtering using single CZTS target with sulfurization process. In order to study the effect of surface treatment using ammonia solution, solution temperature was varied. Structural properties of the samples are almost same with and without ammonia surface treatment measured by XRD and Raman spectroscopy. From the measurement of the chemical composition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A large number of theoretical studies have been reported for heterostructure solar cells. Band‐gap matching is an efficient strategy for exploring the possibilities of phosphorene in photovoltaics, which saves time and materials as compared to trial‐and‐error experimental processes . For instance, bilayer phosphorene/MoS 2 heterostructures have a theoretical conversion efficiency of up to 18%, which exceeds that of graphene/ transition metal dichalcogenide (TMDC) counterparts .…”
Section: Photovoltaic Device and Solar Cellsmentioning
confidence: 99%
“…A large number of theoretical studies have been reported for heterostructure solar cells. Band‐gap matching is an efficient strategy for exploring the possibilities of phosphorene in photovoltaics, which saves time and materials as compared to trial‐and‐error experimental processes . For instance, bilayer phosphorene/MoS 2 heterostructures have a theoretical conversion efficiency of up to 18%, which exceeds that of graphene/ transition metal dichalcogenide (TMDC) counterparts .…”
Section: Photovoltaic Device and Solar Cellsmentioning
confidence: 99%
“…24 electrodeposition, and SILAR on different substrates. [33][34][35][36][37] These methods have their drawbacks such as using complex equipment, with a very high cost for physical methods and harsh chemical processes, conditions for a severe chemical reaction, and toxicity for chemical methods. The hydrothermal method has been widely utilized to synthesize high-quality nanocrystals with distinctive morphology crystal structure and low-cost manufacture.…”
mentioning
confidence: 99%